2016
DOI: 10.1037/drm0000036
|View full text |Cite
|
Sign up to set email alerts
|

Violence, sex, and dreams: Violent and sexual media content infiltrate our dreams at night.

Abstract: Many people today are immersed in media similar to fish in water. Electronic devices provide virtually unlimited access to media. Although people consume media during their waking hours, the media they consume might also affect their dreams during sleeping hours. The media often contain violence and sex. On the basis of cognitive neoassociation theory, we predicted that violent and sexual media content would prime related thoughts in semantic memory. In this study, 1,287 Turkish participants completed a survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 13 publications
2
8
0
Order By: Relevance
“…This is a particularly relevant result, as extant literature regarding the impact of experimental presleep film stimuli on dream content tends to report low effect scores (Hobson, Pace-Schott, & Stickgold, 2000). Still, and in line with this article, a recent study by Van den Bulck, Çetin, Terzi, and Bushman (2016) shows a clear effect of media content on dream content.…”
Section: Resultssupporting
confidence: 86%
“…This is a particularly relevant result, as extant literature regarding the impact of experimental presleep film stimuli on dream content tends to report low effect scores (Hobson, Pace-Schott, & Stickgold, 2000). Still, and in line with this article, a recent study by Van den Bulck, Çetin, Terzi, and Bushman (2016) shows a clear effect of media content on dream content.…”
Section: Resultssupporting
confidence: 86%
“…We proposed pre-sleep cognitive arousal as an additional explanation and tested its mediating effect between automatic TikTok use and daytime fatigue. Such a mediating effect was indeed observed, both supportive of hypothesis H 2 and in line with a prior study suggesting that the disturbance caused by media content is still at play in the absence of sensory instigation (Van den Bulck et al, 2016): Specifically, the chronic effect of media exposure may infiltrate the cognitive system without conscious control. Automatic TikTok use may simply raise the odds of people coming across arousing content, which is relatively popular on the platform (BBC, 2020), and may lead to more overall time spent on TikTok, thereby aggravating daytime fatigue.…”
Section: Direct and Indirect Association Between Automatic Tiktok Use...supporting
confidence: 88%
“…More specifically, researchers argue that arousal created by media content consumed before falling asleep exerts an influence on viewers' cognitions before and even while sleeping (Van den Bulck et al, 2016). Two more studies focusing on TV viewing found that pre-sleep cognitive arousal explains why viewers feel increased fatigue during the day, and that TV viewing is responsible for daytime dysfunction (Exelmans & Van den Bulck, 2017a;.…”
Section: The Mediating Role Of Pre-sleep Cognitive Arousalmentioning
confidence: 99%
“…The quite frequent occurrences of fantasy/prehistoric animals in the dreams of children and adolescents indicate that media might have an effect on dreams about animals. Whereas the effect of media on dreams have been demonstrated (Moverley et al., 2018; Stephan et al., 2012; Van den Bulck, 2004; Van den Bulck et al., 2016), systematic studies as to whether media animals show up in dreams have not yet been carried out.…”
Section: Discussionmentioning
confidence: 99%